Forgo or Go for One? The Unavailable Effect in Non-comparable Choice Sets - Tian, Jing; Chen, Rong; He, Feng (Frontiers in Psychology, 2019)
This research aimed to explore how consumers’ purchase behavior varies when they are faced with unavailable options in a non-comparable choice set. We investigated the unavailable effect based on goal-related mindsets theory and found that consumers with an activated which-to-buy mindset show higher purchase intention for the remaining options relative to those who have a whether-to-buy mindset. Four between-subject experiments were undertaken. Study 1 (including two experiments, both two groups) depicted the relationship between the mindset and consumer purchase choice. Study 2 examined the construal level as the underlying mechanism. Two further studies enabled two methods, such as shopping cart state and payment type, to activate different mindsets and found the boundary conditions of each method. Study 3 found that empty cart (vs. non-empty cart) activate whether-to-buy mindset restraining purchase intention, while the habitual (vs. non-habitual) initial purchase moderated the shopping cart effect. Study 4 found that paying by gift cards (vs. gifted cash) primed which-to-buy mindset increasing purchase intention, while the payment effect declined when the product was high in feasibility (vs. desirability). The insights gained from this research can guide both online and offline retailers in how to strategically manage consumer mindsets under unavailable circumstances. Optimal presenting timing and method of unavailable information may activate a different mindset and help boost sales of the remaining options at the same time.